CROSS-SECTIONAL ASSESSMENT OF HEMATOLOGICAL AND BIOCHEMICAL PROFILES IN HELICOBACTER PYLORI-POSITIVE INDIVIDUALS - REHMAN, AU; KHAN, K; ULHAQ, I; NOOR, S; ALI, A; ULLAH, U; RAHEEM, MF; HAQ, A (Biological and Clinical Sciences Research Journal, 2024)
Helicobacter pylori (H. pylori) infection is a prevalent condition known to affect various hematological and biochemical parameters. Understanding its prevalence and associated blood parameter alterations can provide valuable insights into its clinical implications. Objective: To determine the prevalence of H. pylori infection in District Peshawar KP and its association with complete blood count (CBC) and biochemical parameters to establish a clear relationship between H. pylori infection and these variables. Methods: A longitudinal investigation involved 300 individuals from District Peshawar KP. Blood samples were collected from positive and negative participants for H. pylori infection. These samples were analyzed for various hematological and biochemical parameters, including red blood cell (RBC) count, hemoglobin (Hb) concentration, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), white blood cell (WBC) count, platelet count (PLT), vitamin D levels, urea, and serum glutamic-pyruvic transaminase (SGPT/ALT) levels. Statistical analysis was performed to identify significant associations. Results: The prevalence of H. pylori infection was 57.7% (n=173), with 42.3% (n=122) testing negative. Gender distribution showed 39.7% males (n=119) and 60.3% females (n=181). Age distribution included 17.3% (n=52) aged 2-20 years, 48.5% (n=146) aged 21-40 years, 28.3% (n=85) aged 41-60 years, 5% (n=15) aged 61-80 years, and 0.7% (n=2) over 80 years. Hematological parameters were as follows: RBC count 4 ± 3.1 × 10^6/µL, Hb concentration 13.4 ± 1.64 g/dL, MCV 81 ± 7.8 fL, MCH 27 ± 3.8 pg, MCHC 33.9 ± 24.9 g/dL, WBC count 10 ± 12 × 10^3/µL, and PLT count 30 ± 83 × 10^3/µL. Significant relationships (p < 0.05) were observed between H. pylori infection and alterations in these blood parameters. Vitamin D levels averaged 39 ± 21, and ALT levels were significantly higher in H. pylori-positive cases (32.7 ± 14). Conclusion: This study demonstrates a significant prevalence of H. pylori infection in District Peshawar KP and its association with various hematological and biochemical parameters. The findings suggest that H. pylori infection may have notable effects on blood parameters, highlighting the need for further research to understand the clinical implications and to guide future studies in this area.